Exploring quality and its value in the Italian olive oil market: A panel data analysis - Anna Carbone; Luca Cacchiarelli; Valentina Sabbatini (Agricultural and Food Economics, 2018)
Olive oil markets, both traditional and new ones, are changing rapidly with vertical as well as horizontal differentiation that increasingly play a role in featuring demand and supply. The paper explores the role and effectiveness of different quality clues in the creation of value in high segments of the Italian olive oil market by applying a hedonic price model. Data come from one of the oldest and most reputed Italian guides Flos Olei which reviews around 250 Italian producers and their products. The study covers three production years (from 2012 to 2014) so that, besides the OLS estimations, a panel data analysis is also conducted. Main results indicate that consumers give value to features directly related to the product, as well as to the raw material used and to the production process; also, the kind of producer and the production area affect price. Moreover, the analysis shows the emerging role of experts in releasing valuable information about quality. On the contrary, European quality schemes, such as those for product origin and for organic production, do not bring additional value to consumers in the explored high market segments.
Keywords: D12; Q13; 330; Flos Olei olive oil guide; Quality clues; Hedonic price model; OLS; Panel regression